Training on Repairing the Winding Coil of a 1-Phase Electric Water Pump Motor - Cahyadi, Catra Indra; Usman, Usman; Amren, Hairul; Pasa, Inda Tri; Nur, Fauziah; Wardani, Ivana; Putra, Angga Amanda; Samosir, Ronaldo (Asosiasi Profesi Multimedia Indonesia, 2023)
Training skills and how the steps are learned as a learning activity for trainees, as well as starting from the theory about electric motors and practicing sequentially. Understanding each material given in the module is also needed to identify the coil winding of a 1 phase electric motor, especially a water pump. Learning activities are equipped with exercises or evaluations that become a benchmark for the training participants' mastery level. Trainees are expected to understand the explanation from the teaching team so that they can understand well the material that is the basis of repair planning, installing winding sleeves at Cern, winding copper email wire windings to mall boards, attaching windings to the grooves of water pump motors, connecting the main and auxiliary winding coils, tying the windings with nylon thread After finishing winding the wire coil, close the water pump motor that is ready to be rolled again and then test the motor that has been completed in rolling again. After participating in all learning activities in this training, participants are expected to follow the procedures from the planning stages of rolling, installing coil windings, and reinstallation for the quality of winding coils, with good quality and neatness.